Elastoplastic mechanical behavior analysis of surface-coated Zircaloy-4 cladding under multi-field coupling - Xin Wang; Ze Xu; Yulan Liu; Biao Wang (Nuclear Engineering and Technology)
The elastoplastic mechanical behavior of Zircaloy-4 (Zr-4) cladding, coated with chromium (Cr) or FeCrAl on its surface, is explored under the coupled effects of multi-field coupling. Utilizing the Finite Element Software ABAQUS, simulations are conducted to calculate the evolution of stress and strain over two complete fuel cycles. Comparisons are drawn between the coated and uncoated Zircaloy-4 cladding materials. The results indicate that the application of surface coatings significantly mitigates stress levels in the cladding during the first fuel cycle. During the second fuel cycle, all three types of cladding exhibit relatively minor plastic strain, which is attributed to the unloading and reloading process between cycles. Notably, the plastic zone propagates from the interior to the exterior of the cladding. When compared to traditional Zircaloy-4 cladding, the coated cladding exhibits improved elastoplastic mechanical behavior. The operational mechanism of the coating for different stresses in cylindrical coordinates and its response to unloading and reloading cycles are also investigated. Specifically, the coated claddings exhibit an evident delay in reaching full plasticity compared to uncoated claddings. Furthermore, FeCrAl coating material initially shows good performance, and it needs to be verified in more aspects in the future. Results and Conclusions in this paper can provide reference and guidance for future experiments.